Artificial Intelligence in criminalistics: new dimensions of AI Copywriting - Endre Nyitrai (Belügyi Szemle, 2025)
Aim: To present research opportunities in the field of generative artificial intelligence in forensic science. The study seeks to answer the question of how AI can transform the effectiveness of investigations.